The Princess diaries - Marshall, Garry; Houston, Whitney; Chase, Debra Martim; Iscovish, Mario; Walt Disney Pictures; Brownhouse production (Burbank, CA : Walt Disney Home Entertainment : distributed by Buena Vista Home Entertainment, 2001)
Mia is a frizzy-haired, glasses-wearing 15-year-old girl whose two highest ambitions are to become invisible and to get a few kisses from an attractive school heartthrob. She is stunned and horrified when her coolly continental grandmother shows up and informs her that she's the crown princess of the European principality Genovia. Soon enough, Mia has to undertake'princess lessons' (and a makeover) from her queenly grandmother, and eventually she blossoms into a confident, radiant girl
Title from title screen
Subtitles in English, Mandarin, Bahasa, Thai and Korean
Director of photography, Karl Walter Lindenlaub ; editor, Bruce Green ; music, John Debney ; costume designer, Gary Jones ; production designer, Mayne Berke ; screenplay by Gina Wendkos
Casts: Anne Hathaway, Heather Matarazzo, Hector Elizondo, Mandy Moore, Caroline Goodall, Robert Schwartzman, Erik Von Detten, Julie Andrews
Keywords: Princesses -- Drama; High school students -- California -- San Francisco -- Drama; Comedy films